2012
DOI: 10.1590/s0100-06832012000400024
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties and particle-size fractions of soil organic matter in crop-livestock integration

Abstract: SUMMARYCrop-livestock integration represents an interesting alternative of soil management, especially in regions where the maintenance of cover crops in notillage systems is difficult. The objective of this study was to evaluate soil physical and chemical properties, based on the hypothesis that a well-managed croplivestock integration system improves the soil quality and stabilizes the system. The experiment was set up in a completely randomized design, with five replications. The treatments were arranged in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
3
12
0
4
Order By: Relevance
“…These greater TC contents in the NCA were related to its greater amount of plant residues on the soil surface due to the vegetation in this area and the absence of human disturbances. Similar results were reported by Batista et al (2013), Tirloni et al (2012) and Gazolla et al (2015), who found greater TOC contents in areas of native vegetation compared with CLI areas. Table 2.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…These greater TC contents in the NCA were related to its greater amount of plant residues on the soil surface due to the vegetation in this area and the absence of human disturbances. Similar results were reported by Batista et al (2013), Tirloni et al (2012) and Gazolla et al (2015), who found greater TOC contents in areas of native vegetation compared with CLI areas. Table 2.…”
Section: Resultssupporting
confidence: 89%
“…Rossi et al (2012) compared CLI and native areas (Cerrado) in the same region of the present study and found greater OCp and smaller OCm contents in the soil layer 0,0-0,20 m of the CLI area. Tirloni et al (2012) found similar values of OCp and OCm in CLI and native forest areas. Carmo et al (2012) evaluated an Oxisol area under CLI in the Cerrado biome and found greater OCp and OCm contents in the CLI compared with the native vegetation area.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Therefore, knowing soil structural quality and its variation throughout the time is crucial to predict such effects (VIANA et al, 2004). This way, several researches have been carried out to draw structural quality indexes by monitoring the effects of management practices on soil physical, chemical, water and biological attributes (BERGAMIN et al, 2010;LIMA et al, 2012;OLIVEIRA et al, 2004;SEVERIANO et al, 2009); besides organic matter dynamic along its profile (COSTA JUNIOR et al, 2012;SILVA et al, 2013;TIRLONI et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it noteworthy to mention that proper morphometric conditions will be find in soils under original vegetation; since it has no human action and increased organic matter level, contributing to structure stability (COSTA JUNIOR et al, 2012;SALTON et al, 2008;TIRLONI et al, 2012). Unfortunately, these conditions change when inserted into a productive process and which therefore changes soil structuring at different magnitude levels (OLIVEIRA et al, 2004;SEVERIANO et al, 2009).…”
Section: Introductionmentioning
confidence: 99%